2017
DOI: 10.1146/annurev-micro-090816-093754
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Biogenesis

Abstract: The hallmark of Gram-negative bacteria and organelles such as mitochondria and chloroplasts is the presence of an outer membrane (OM). In bacteria such as Escherichia coli, the OM is a unique asymmetric lipid bilayer with lipopolysaccharide (LPS) in the outer leaflet. Integral, transmembrane proteins assume a β-barrel structure (OMPs) and their assembly is catalyzed by the heteropentomeric Bam complex containing the OMP BamA and four lipoproteins, BamB-E. How the Bam complex assembles a great diversity of OMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
243
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(247 citation statements)
references
References 99 publications
(179 reference statements)
2
243
0
2
Order By: Relevance
“…The BAM complex and its role in insertion of β-barrel proteins into the OM has been defined in considerable structural and mechanistic detail (Konovalova et al, 2017;Noinaj et al, 2017). There is also increasing appreciation that the BAM complex plays a broader role in crafting the protein landscape at the cell surface (Pavlova et al, 2013;Konovalova et al, 2014;Bernstein, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The BAM complex and its role in insertion of β-barrel proteins into the OM has been defined in considerable structural and mechanistic detail (Konovalova et al, 2017;Noinaj et al, 2017). There is also increasing appreciation that the BAM complex plays a broader role in crafting the protein landscape at the cell surface (Pavlova et al, 2013;Konovalova et al, 2014;Bernstein, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Intimate structural synergy is now recognized between the peptidoglycan and the teichoic acids of the Gram‐positive bacteria, and between the peptidoglycan and the outer membrane of the Gram‐negative bacteria . Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram‐positive bacteria and with respect to lipopolysaccharide transport in Gram‐negative bacteria . Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope‐targeting Antibioticsmentioning
confidence: 99%
“…77,78 Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram-positive bacteria 69,[79][80][81][82][83][84] and with respect to lipopolysaccharide transport in Gram-negative bacteria. [85][86][87][88][89][90] Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope-targeting Antibioticsmentioning
confidence: 99%
“…These membranes have diverse lipid compositions and are active participants in essential biological processes . The outer membrane of Gram‐negative bacteria is the first of the three layers that surround the bacterial cytoplasm . This bilayer is highly asymmetric: the inner leaflet is mainly built by various species of phospholipids, while the outer leaflet is largely composed of lipopolysaccharides (LPS) .…”
Section: Introductionmentioning
confidence: 99%
“…Biological processes taking place in the bacterial cell envelope are mainly related to the communication of the cell with the external medium, which includes sensing and providing feedback to external conditions . Proteins located within the bacterial cell envelope, including integral membrane proteins, lipidated proteins, peripheral membrane proteins, and soluble proteins, play key roles in these communication events . Lipidated proteins are anchored to biological membranes through a lipid moiety covalently bound to their N‐termini and represent 2–8% of the total predicted proteome in bacteria …”
Section: Introductionmentioning
confidence: 99%